Pengaruh Kualitas Pelayanan Pajak dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak Restoran melalui Kesadaran Pajak sebagai Variabel Intervening : Pada Badan Pengelola Pajak dan Retribusi Daerah Kota Jambi - Bintang Maharani; Hendriyaldi Hendriyaldi; Fitri Widiastuti (Politeknik Kampar, 2025)
This study aims to analyze the effect of tax service quality and tax sanctions on restaurant taxpayers' compliance through tax awareness as an intervening variable at the BPPRD of Jambi City. The background of this study is the delay in reporting, payments, and tax arrears of restaurants in Jambi City. The research method used is a quantitative approach with data collection techniques using questionnaires distributed to 72 restaurant taxpayers, selected based on the Slovin formula with a 10% margin of error. The results of the instrument test show that the data obtained are valid and reliable. The findings reveal that tax service quality and the implementation of tax sanctions have a positive and significant impact on tax awareness and taxpayer compliance. In addition, tax awareness acts as a mediating variable that strengthens the relationship between service quality and tax sanctions with restaurant taxpayers' compliance. Therefore, improving the quality of tax services and applying stricter sanctions can effectively encourage the increased compliance of restaurant taxpayers in Jambi City.